Economic valuation of wetland ecosystems in Paya Indah Wetlands, Selangor, Malaysia - Siew, Mei Kuang (2014)
Wetlands provide numerous ecosystem goods and services that are important to development and survival of humanities. They provide food and clean drinking water, offer a unique habitat for many different species and provide hydrologic functions as well as support in industries such as tourism and recreation. The public good characteristics and open access nature of wetlands often result in wetlands being undervalued in decision about their use. Many policies and decisions do not take into account the many goods and services that wetlands provide and thus leading to the rapid degradation and wetlands loss. Economic valuation of wetland ecosystem goods and services aims to investigate public preferences and to quantify these goods and services in monetary term. Paya Indah Wetlands is a human-made wetland, which was formerly a mining site. Economic valuation of Paya Indah Wetlands can play an important role in determining appropriate trade-off between wetland conservation and profitable development projects that result in biodiversity loss. The objective of this study is to estimate the economic value of wetland goods and services provided by Paya Indah Wetlands. In this study, the total economic value was captured which was the sum of all direct and indirect use value plus non-use values of the wetland ecosystem services. Contingent valuation method was employed to estimate the willingness to pay of domestic visitors to Paya Indah Wetlands. The data were collected through face-to-face interview. Findings of the study have revealed that Paya Indah Wetlands contributes an estimated annual value of RM 349, 604. In addition, the domestic visitors to Paya Indah Wetlands were willing to pay RM 7.39 as entrance fee per person. The price of entrance fee and respondent income were the significant determinants and influenced visitors‟ willingness to pay. Results of this study provide evidence of the importance of sustaining and enhancing those resources and the ecosystems that provide them. This suggests that the policy and decision makers should incorporate the full economic value of wetlands into decision about whether to conserve or converse the wetland ecosystems for achieving sustainable use and management of wetlands. Results of this study also facilitate in establishing an efficient and realistic pricing policy for Paya Indah Wetlands, which would help in reducing the overcrowding and excessive exploitation of the wetland use.